Advances in Condition Monitoring, Optimization and Control for Complex Industrial Processes (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book documents 25 papers collected from the Special Issue “Advances in Condition Monitoring, Optimization and Control for Complex Industrial Processes”, highlighting recent research trends in complex industrial processes. The book aims to stimulate the research field and be of benefit to readers from both academic institutes and industrial sectors.